Antibacterial effect of acidic ionized water on horse wounds bacterial isolates - Abdul Rahman, Afiqah Zafirah; Mohd Adzahan, Noraniza; Zakaria, Zunita; Mayaki, Abubakar Musa (Veterinary World, 2021)
Background and Aim: Horse wounds can be easily infected with bacteria depending on the nature of its cause such as laceration, abrasion, or puncture as well as the nature of its environment. Various treatments are available in managing open wounds, including the usage of topical antibiotics and antiseptics. However, antibiotic resistance has been a major concern attributed with chronic wound infection. The aim of this study was to test the efficacy of ionized water at different pH against the growth of common bacteria from horse wounds. Materials and Methods: Ten swab samples from equine infected wounds were collected and bacteria isolation and identification were performed. The antibacterial effect of the ionized water of pH 2.5, 4.5, 7.0, and 11.5 was tested on Staphylococcus aureus, Staphylococcus pseudintermedius, Staphylococcus intermedius, Escherichia coli, Pantoea agglomerans, and Klebsiella pneumoniae. The time-kill profiles of the ionized waters were determined at time 0, 2, 4, 6, and 8 h. Results: Ionized water of pH 2.5 and 4.5 showed antibacterial activity against S. aureus, S. pseudintermedius, and S. intermedius with significant (p>0.05) reduction in colony-forming unit/mL within 2-8 h. The degree of bactericidal effect of the acidic ionized water differs between the species with S. intermedius more susceptible. However, there was no antibacterial effect at pH 2.5, 4.5, 7.0, and 11.5 on the Gram-negative bacteria tested. Conclusion: Ionized water of pH 2.5 and 4.5 is effective in minimizing the growth of Gram-positive bacteria; thus it could be of clinical importance as an antiseptic for surface wound lavage in horses.